Comparative study of single-hole orifice and perforated plate for flow balancing in aircraft ECS - Kurukulasuriya Ranga Prabath Dias. (2013)
This project simulates and compares the performance of two types of flow restrictors, namely single-hole orifice plate and a perforated plate with similar environmental control systems (ECS) of aircraft’s pressure and flow rate conditions which are ranged from 2988 Pa to 3735 Pa (12-15 inches of water) and 0.04719m3/s to 0.37755m3/s (100 to 800 CFM). The airflow models are studied using Computational Fluid Dynamic (CFD) solver ANSYS 13 and FLUENT with multiple models and varying characteristics, such as orifice geometry in terms of β ratio (dimensionless ratio of orifice hole diameter to pipe diameter ), pressure and inflow rate. The focus of the study is directed towards the change of Reynolds numbers commonly associated with pipeline transportation of air which is from 3,800 to 30,300 Reynolds numbers.